(untitled) (Proceedings of International Educators Conference, 2023)
Much vocabulary is learned without formal teaching. We gain words from conversation, observation, television/media, and reading. However, research shows that explicitly teaching vocabulary can measurably improve reading comprehension — if we teach the right words well enough. Here are five key principles to effective vocabulary instruction.